Efficacy, safety, and tolerability of lifitegrast 5% eye drops: A randomized, double-blind, active-controlled trial in Indian patients with dry eye disease - Namrata Sharma; Sayan Basu; Rohit Shetty; Pramod Kumar; Anindita Mondal; P Seshu Babu; Richa Srivastava; Ranjana A Pande; Shubashree Karat; Hemaxi P Desai; S Manjula; M Krishna Kumar (Indian Journal of Ophthalmology)
Purpose: To compare the efficacy, safety, and tolerability of lifitegrast 5% versus carboxymethylcellulose (CMC) 0.5% in adult patients with dry eye disease (DED). Methods: A total of 370 eligible patients with DED were randomized equally to receive twice-daily doses of a single drop in each eye of either lifitegrast 5% or CMC 0.5% for 12 weeks. Follow-up at weeks 2, 6, and 12 evaluated changes from baseline in primary [eye dryness score (EDS), ocular discomfort score (ODS), ocular surface disease index (OSDI), and tear film break-up time (TFBUT)] and secondary [Schirmer tear test (STT) score and corneal fluorescein staining (CFS) score] endpoints. Global improvement, safety, and tolerability were also assessed. Results: At week 2, values of ocular discomfort score, OSDI, and conjunctival redness were significantly more favorable in patients treated with lifitegrast compared to CMC. At week 6, values of all study variables were better in patients treated with lifitegrast compared to CMC; differences between the groups were statistically significant for all except photophobia. This trend was also maintained at week 12. Global improvement and tolerability were found to be better with lifitegrast than with CMC. No serious safety concerns were reported in any treatment group. Conclusion: To our knowledge, this is the first active-controlled trial informing on the efficacy, safety, and tolerability of lifitegrast 5%. Significantly more favorable values for EDS (except photophobia), ODS, OSDI, TFBUT, STT score, CFS score, and conjunctival redness score were achieved at week 12 with lifitegrast 5% compared to CMC 0.5%.